Sinonasal teratocarcinosarcoma: is minimally invasive resection followed by adjuvant histology directed chemo-radiation a better alternative to radical excision? Case report - Singh, N. Dhaneshwar; Sen, Kanwar; Sharma, Arun; Bharadwaj, Meenakshi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Sinonasal teratocarcinosarcoma (SNTCS) is a rare higly malignant tumour occuring almost exclusively in the sinonasal tract. This aggressive tumour arising from the primitive embryonic or immature pluripotential cells of olfactory epithelium has high propencity for loco-regional recurrence and mortality. SNTCS generally presents with relatively benign symptoms like nasal obstruction and recurrent epistaxis in its early stage. In advance stage with orbital and intracranial spread other symptoms raising suspicion of malignancy, such as dysphagia, odynophagia, epiphora, vision loss, exophthalmos, anosmia, headache and altered sensorium appears. In view of its aggressive behaviour, radical excision with or without chemoradiation is advocated as the optimum treatment. Local recurrence of SNTCS after excision has been reported as high as 45% with a mean recurrence time of 21.3 months. Even though distant metastasis is rare, local recurrence frequently leads to treatment failure and subsequent death. Here we share our experience of SNTCS in a 23 year old male managed with endoscopic craniofacial resection followed by histocytology directed chemotherapy with external beam radiation. He remains disease free in last 3 years of follow up.